A NEW SCREENING TOOL FOR SARCOPENIA: THE SARCOPENIA EVALUATION MEASUREMENTS (SEMS). (11th November 2018) - Su, L; Cao, L; Wang, H; Hai, S; Dong, B
Abstract: Sarcopenia is related to higher adverse events in community dwelling older adults. However, it lacks powerful and convenient screening tools. Our team developed a new screening tool name Sarcopenia Evaluation Measurements (SEMs), which was objective, convenient and with relatively high sensitivity and specificity. The SEMs is composed of measurements of muscle mass via biceps circumference and calf circumference using mean-SD as cutoffs, as well as muscle strength via walking speed and handgrip using cutoffs proposed by Asian Working Group for Sarcopenia (AWGS). Both muscle mass and muscle strength having at least one declined measurement was considered as sarcopenia. A diagnostic accuracy study was performed in a community in Chendu, China with participants older than 60 years old and sarcopenia diagnosed using AWGS criteria with bioelectrical impedance analysis. A total of 922 participants were included in this analysis, with 448 men (48.6%) and 474 women (51.4%). The mean age of the participants was 68.7 ± 6.5 years, and 84 (9.1%) were diagnosed as sarcopenic patients according to AWGS definition. The AUC of SARC-F, SARC-CalF and SEMs were 0.527, 0.633 and 0.789, respectively. The sensitivities were 5.95% (1.96%-13.35%), 34.52% (24.48%-45.69%), and 58.14% (95% CI=47.01%-68.70%); specificities were 99.40% (98.61%-99.81%), 92.12% (90.09%-93.86%), and 99.52% (98.79%-99.87%); PPV were 50.00% (22.81%-77.19%), 30.53% (23.20%-38.99%), and 92.59% (82.23%-97.12%); NPV were 91.33 % (90.89%-91.75%), 93.35% (92.31%-94.26%), and 95.88% (94.77%-96.76%); and accuracy were 90.88% (88.83%-92.66%), 86.88% (84.52%-88.99%) and 95.69% (94.17%-96.90%) for SARC-F, SARC-CalF and SEMs, respectively. The SEM is an objective, convenient, sensitive screening tool for sarcopenia.